DESIGNING CBA MODEL OF PERFORMANCE APPRAISAL SYSTEM AS A MERIT RATING FOR HIGHER EDUCATION INSTITUTION - Tjahjani Prawitowati (Journal of Economics, Business, and Accountancy Ventura, 2011)
Performance appraisal system as part of human resource management tools for higher edu- cation institution plays an important role in motivating and increasing educators and sup- porting staff’s performance. It is very valuable for higher education institutions. Yet, in edu- cation affairs, this is still considered less. This research attempts to design competence-based performance appraisal system for higher education institution. Depth interview, secondary data, and questionnaire are used as the instruments. It is conducted in three types of higher education in Indonesia. In terms of professionalism, social competence, and pedagogical competences, it is found that there are three competencies, namely core competency, mana- gerial competency, and technical competency. Core competency is referred to organization’s value, varied among higher education institutions, but mostly includes integrity, customer orientation,  achievement  orientation,  initiative,  teamwork,  empathy,  and  adaptability.  In terms of managerial competencies, most higher education institutions consider planning, problem solving, influencing others, empowerment, supervising, and controlling. For techni- cal competencies, they include computer literacy, English mastery and job technical mastery.